„Österreichische“ und andere Ironie in den Texten von Olga Flor, Teresa Präauer und Cordula Simon - Kupczyńska, Kalina (Studia Germanica Posnaniensia, 2020)
“There is a tradition of irony in Austria, not only in literature”, said Kathrin Röggla in an interview in 2012; my article considers the assertion as a starting point to an analysis of three novels by contemporary Austrian women authors Flor, Präauer and Simon. The aim is to examine the different patterns of irony by Flor, Präauer and Simon in order to assess what the “Austrian” concept of irony can mean today. Furthermore, I would like to consider the „Austrian“ irony as a specific Austrian cue to express involvement in current political matters.